Impacts of Artificial Intelligence on Teachers’ Role in Lalbandi Municipality, Sarlahi, Nepal - Sah, Nawal Kishor (Janajyoti Journal, 2025)
Artificial Intelligence (AI) is the field of computer science which trains machines to imitate intelligent human abilities such as learning, reasoning, and decision-making. Integration of AI in education has the potential to transform traditional teaching techniques and enhance student achievement, especially in Lalbandi Municipality, Sarlahi District, Madhesh Province, Nepal. The aim of this study is to examine the potential effects of AI on the roles, responsibilities, and professional development of educators in this field. The study determines the levels of concern, confidence, attitudes, and perceived usefulness towards AI among educators by combining a comprehensive literature analysis with primary research including 70 teachers from community and private school. The results show that there is a lot of ambiguity regarding the ways in which AI may impact decision-making, job security, and trustworthiness of AI training and its advantages. To address these issues, researcher suggests to improve teachers' self-assurance and comprehension of AI, and cultivate a more positive attitude toward AI technologies. The study emphasizes the critical need for focused AI training and support programs. These findings are essential for creating a context-specific strategy for integrating AI into education that puts teachers' needs and agency first, with the ultimate goal of improving Nepal's educational system.